Optical Response of MoTe2 and WTe2 Weyl Semimetals: Distinguishing between Bulk and Surface Contributions. Issue 3 (29th January 2020) - Popescu, Adrian; Pertsova, Anna; Balatsky, Alexander V.; Woods, Lilia M.
Abstract: A first‐principles investigation of the optical response of the Weyl Semimetals MoTe 2 and WTe 2 is presented. The approach, based on combining two formulations, allows to both separate the intraband and interband parts of the optical conductivity and to distinguish between the bulk and surface contributions to the optical response. It is found that the response is truly anisotropic, with peaks that can be associated with interband transitions involving either bulk or surface states. The role of the relaxation time, and the relation of the calculated results with available experimental measurements, are also discussed. Furthermore, the approach reported is transferable to any system, topologically trivial or non‐trivial, thus addressing the long‐standing need for comprehensive characterization of the optical response. Abstract : A general computational approach for bulk and surface optical response in materials is proposed. Within this method, one can distinguish between interband and intraband components and bulk and surface contribution in a semi‐infinite material. This approach is able to give insight into the optical spectrum of the Weyl semimetals MoTe2 and WTe2 .